A review of the impact of shift-work on occupational cancer: part 1 – epidemiological research. Issue 1 (2nd January 2018) - McElvenny, D. M.; Crawford, J. O.; Davis, A.; Dixon, K.; Alexander, C.; Cowie, H.; Cherrie, J. W.
Abstract: There are a growing number of studies suggesting a link between night shift work and increased risk of certain types of cancer, including breast cancer. In 2007, the International Agency for Research on Cancer described shift work involving circadian disruption as probably carcinogenic to humans. A systematic review of the epidemiology on shift work and cancer from 2005 to 2015 was carried out. We used standard systematic review methodology to identify, critically appraise and summarize the relevant epidemiological literature. We looked at reviews and meta-analyses from 2005 to 2015 and recent studies published from 2013 to 2015. For breast cancer, the relative risks of working night shifts have been reducing from 1.5 to around 1.2 over the past decade. A recent meta-analysis of prospective cohort studies has suggested that the overall relative risk of breast cancer may not be raised at all. The evidence for a raised risk of cancers other than breast cancer remains somewhat limited. The epidemiological evidence suggests that if a cancer risk exists from occupational exposure to night shift work, then the relative risk will be no more than around 1.1 or 1.2 and indeed may not exist at all.